Honeycomb ceramic supported denitration catalyst, preparation method thereof and flue gas denitration method
By modifying TiO2 with Si and preparing Ti-Si modified TiO2 hollow microspheres by hydrothermal method, the problems of small specific surface area and low mechanical strength of honeycomb SCR denitrification catalysts were solved, and the preparation of efficient honeycomb ceramic-loaded denitrification catalysts was achieved, thereby improving high-temperature activity and denitrification efficiency.
Patent Information
- Application Number
- CN202410445768.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-12
- Publication Date
- 2025-10-21
AI Technical Summary
The existing honeycomb SCR denitrification catalyst has a small specific surface area, insufficient internal pores, easy aggregation of active ingredients, low mechanical strength, and cannot maintain high catalytic activity under high reaction space velocity conditions. In addition, the TiO2 crystal transformation affects high-temperature performance.
By modifying TiO2 with Si and combining it with a hydrothermal method to prepare Ti-Si modified TiO2 hollow microspheres, the coated catalyst slurry is coated on the honeycomb ceramic substrate to prepare a honeycomb ceramic supported denitrification catalyst, thereby increasing the specific surface area and mechanical strength and improving the distribution of active ingredients.
The high-temperature thermal stability and activity of the catalyst are improved, the geometric specific surface area is increased, and high activity is ensured in an environment of 300-500°C, which reduces the production cost and improves the denitrification efficiency.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of SCR denitration reaction, and in particular to a honeycomb ceramic supported denitration catalyst, a preparation method thereof, and a flue gas denitration method. Background Art
[0002] Gas boilers are important energy equipment for industrial production and are indispensable in the process of oil refining. As the scale and process level of refining equipment continue to increase, gas boilers are required to operate smoothly and meet standards. Natural gas, as the main fuel for gas boilers, has the advantages of low nitrogen, low sulfur and low dust emissions. However, due to the large amount of combustion air injected, nitrogen in the air will produce a large amount of NO under high temperature conditions. x .
[0003] Based on the different molding methods, SCR denitrification catalysts are divided into corrugated plate, honeycomb, and plate types to meet the requirements of different flue gas operating conditions. Most SCR catalysts are mainly honeycomb-shaped. For ethylene cracking furnace gas boilers, due to the high manufacturing cost of the cracking furnace body and the small flue gas denitrification space provided, a higher reaction space velocity is required to meet the denitrification requirements. Therefore, the catalyst needs to be processed into a honeycomb catalyst with a larger number of pores to increase its geometric specific surface area. However, as the number of pores in the honeycomb catalyst increases, higher requirements are placed on the mold. Moreover, as the number of pores in the honeycomb catalyst increases, cracks tend to form during extrusion or it tends to stick to the mold, resulting in a low molding rate and low mechanical strength, wasting manufacturing resources and increasing costs. Therefore, the number of pores in the honeycomb catalyst is generally within 40×40. Therefore, to meet the needs of higher space velocity denitrification, corrugated plate denitrification catalysts are generally used. However, corrugated plate denitrification catalysts are difficult to process and have low mechanical strength.
[0004] In addition, traditional industrial denitrification catalysts with V2O5 as the active component and TiO2 as the carrier have an active temperature range of 320-420°C. When the temperature exceeds 420°C, the crystal form of TiO2 begins to transform into rutile, which affects the performance of the catalyst.
[0005] CN101721993B provides a preparation method and application of a low-temperature SCR catalyst using cerium-doped TiO2 as a carrier. Ce-doped TiO2 gel is prepared by a sol-gel method, and MnO is loaded by wet ball milling. x The active ingredient is dried, calcined and ground. -1 When the reaction temperature is 150-300℃, the NO removal rate is 85%-98%.
[0006] CN106552652A discloses an F-doped denitration catalyst, in which F is doped on a V2O5-WO3 / TiO2 catalyst; the F-doped TiO2 surface presents a large number of charged oxygen vacancies; after WO3 reacts with the charged oxygen vacancies, the amount of reduced WO3 on the catalyst surface increases; after the reduced WO3 reacts with O2, it is oxidized to WO3, and the O2 gains electrons and is converted into superoxide radicals, thereby promoting the oxidation of NO by the catalyst and broadening the active temperature window (250-400°C) of the V2O5-WO3 / TiO2 catalyst.
[0007] However, the defects of the above-mentioned existing technologies are: the internal specific surface area of the prepared catalyst is small, which affects the catalyst efficiency; the internal pores of the catalyst are not rich enough, and the active ingredients are easy to agglomerate, which affects the distribution and dispersion of the active ingredients; or the catalyst is non-ceramic supported, with low strength and small geometric specific surface area; in addition, due to the transformation of TiO2 crystal form, it cannot be applied to higher catalytic temperatures.
[0008] Therefore, how to modify TiO2 to provide a honeycomb ceramic denitrification catalyst with a large specific surface area, rich internal pores, high strength, and high catalytic activity temperature, so that it can have a high catalytic efficiency under high reaction space velocity conditions, is a technical problem that needs to be solved urgently in this field. Summary of the Invention
[0009] To address the above technical issues, the present invention provides a honeycomb ceramic-supported denitration catalyst, its preparation method, and a flue gas denitration method. By modifying TiO2 and preparing a coated catalyst slurry, the honeycomb ceramic catalyst loaded with this slurry possesses a high specific surface area and high denitration efficiency.
[0010] To achieve the above object, the present invention provides a method for preparing a honeycomb ceramic supported denitration catalyst, wherein the method comprises the following steps:
[0011] (1) placing a cordierite honeycomb ceramic substrate in an alkaline solution for etching to obtain a pretreated honeycomb frame carrier;
[0012] (2) mixing a titanium source precursor, a silicon source precursor and an organic alcohol to obtain a mixed solution, performing a hydrothermal reaction, and obtaining Ti-Si modified TiO2 hollow microspheres after a first drying and a first calcination;
[0013] (3) adding water to Ti-Si modified TiO2 hollow microspheres, vanadium source precursor, tungsten source precursor, binder, dispersant, pore-forming agent, and buffer and then ball milling to obtain a coated catalyst slurry;
[0014] (4) The coated catalyst slurry is coated on the pretreated honeycomb frame carrier, and then aged, dried for the second time, and calcined for the second time to obtain a honeycomb ceramic supported denitrification catalyst.
[0015] According to a specific embodiment of the present invention, preferably, the mass ratio of the silicon source precursor to the titanium source precursor is (3-7):100; the volume ratio of the organic alcohol and the titanium source precursor is (3-10):1; the mass ratio of the vanadium source precursor to the titanium source precursor is (0.2-6.0):100; the mass ratio of the tungsten source precursor to the titanium source precursor is (0.5-8.0):100; wherein, the mass of the titanium source precursor is calculated as TiO2, the mass of the silicon source precursor is calculated as SiO2, the mass of the vanadium source precursor is calculated as V2O5, and the mass of the tungsten source precursor is calculated as WO3.
[0016] According to a specific embodiment of the present invention, preferably, step (1) further includes the steps of ultrasonically cleaning and drying the cordierite honeycomb ceramic substrate before etching, and cleaning and drying with pure water after etching; the drying temperature in step (1) is 70-120°C, preferably 90-110°C, and the drying time is 0.5-10h, preferably 1-3h.
[0017] According to a specific embodiment of the present invention, preferably, the titanium source includes tetrabutyl titanate and / or tetraisopropyl titanate.
[0018] According to a specific embodiment of the present invention, preferably, the silicon source precursor is a soluble silicate substance, more preferably sodium silicate and / or sodium metasilicate.
[0019] According to a specific embodiment of the present invention, preferably, the organic alcohol includes anhydrous ethanol and / or ethylene glycol. Anhydrous ethanol can slowly provide OH - , so that the titanium source combines with it to form titanium hydroxide.
[0020] According to a specific embodiment of the present invention, preferably, the vanadium source includes ammonium metavanadate and / or ammonium vanadate.
[0021] According to a specific embodiment of the present invention, preferably, the tungsten source includes ammonium paratungstate and / or ammonium metatungstate.
[0022] According to a specific embodiment of the present invention, preferably, the temperature of the hydrothermal reaction is 140-220° C., preferably 150-180° C., and the time of the hydrothermal reaction is 6-30 h, preferably 15-24 h.
[0023] According to a specific embodiment of the present invention, preferably, the mass ratio of the binder, dispersant, pore-forming agent and titanium source is (0.5-5.0):(0.2-3):(0.2-2):100, wherein the mass of the titanium source is calculated as TiO2.
[0024] According to a specific embodiment of the present invention, preferably, the binder includes carboxymethyl cellulose and / or hydroxypropyl cellulose.
[0025] According to a specific embodiment of the present invention, preferably, the dispersant includes one or a combination of two or more of polyethylene glycol, polyacrylamide, and polyvinyl pyrrolidone.
[0026] According to a specific embodiment of the present invention, preferably, the pore-forming agent includes polyethylene oxide and / or polymethyl methacrylate.
[0027] According to a specific embodiment of the present invention, preferably, the buffer is aqueous ammonia, and the pH is adjusted to 9-11.
[0028] According to a specific embodiment of the present invention, preferably, in step (1), the concentration of the alkali solution is 0.5-5.0 mol / L, preferably 1.0-4.0 mol / L.
[0029] According to a specific embodiment of the present invention, preferably, the alkali solution includes a sodium hydroxide aqueous solution and / or a potassium hydroxide aqueous solution.
[0030] According to a specific embodiment of the present invention, preferably, the temperature of the etching treatment is 20-200° C., more preferably 50-150° C.; the reaction time of the etching treatment is 1.0-10 h, more preferably 2-5 h.
[0031] According to a specific embodiment of the present invention, preferably, the mesh number of the cordierite honeycomb ceramic is 25-400 mesh, preferably 40-150 mesh. Cordierite honeycomb ceramic is a whole composed of many thin-walled parallel small channels. It has the characteristics of large geometric specific surface area, small thermal expansion coefficient, strong impact resistance, good thermal stability, small pressure drop, short mass transfer distance, etc. The use of cordierite as a matrix is conducive to the entry of reactants and the discharge of products. The inventors of the present invention have found through research that according to the national standard GB / T31587-2015 of honeycomb SCR denitrification catalyst, the axial compressive strength is not less than 2.0Mpa; and when cordierite honeycomb ceramic is used as a matrix and after alkaline etching, its axial compressive strength is not less than 20.0Mpa, which has high mechanical strength. In addition, the maximum number of holes in traditional honeycomb catalysts is 40×40, equivalent to 45 mesh; while cordierite can achieve a hole number of 80×80, equivalent to 183.5 mesh. Therefore, cordierite can better meet the needs of high space velocity and high efficiency denitrification industrial applications in ethylene cracking furnaces.
[0032] According to a specific embodiment of the present invention, preferably, in step (2), the temperature of the first drying is 60-180° C., and the time of the first drying is 1-20 h.
[0033] According to a specific embodiment of the present invention, preferably, in step (4), the temperature of the second drying is 30-120° C., and the time of the second drying is 10-80 h.
[0034] According to a specific embodiment of the present invention, preferably, in step (2), the temperature of the first calcination is 400-680°C, and the time of the first calcination is 2-10 hours. After calcination, the organic alcohol inside the microspheres decomposes, leaving microspaces and micropores, which are conducive to the dispersion of the active ingredients, thereby preventing the aggregation of the active ingredients; at the same time, calcination converts titanium hydroxide (molecules are bound by van der Waals forces) into titanium oxide (atomic bonds are formed between titanium, oxygen, and titanium), making the lattice more stable; calcination also provides the necessary time and space for subsequent chemical reactions.
[0035] According to a specific embodiment of the present invention, preferably, in step (4), the temperature of the second roasting is 450-650° C., and the time of the second roasting is 2-8 hours.
[0036] According to a specific embodiment of the present invention, preferably, the aging temperature is 20-40° C., and the aging time is 12-48 hours.
[0037] According to a specific embodiment of the present invention, preferably, the ball milling time is 1-2 hours.
[0038] According to a specific embodiment of the present invention, preferably, in step (3), the solid content of the coating catalyst slurry is 5%-60%, preferably 20%-40%.
[0039] According to a specific embodiment of the present invention, preferably, in step (4), the coating amount of the coating catalyst slurry is 5-200 g / L, more preferably 25-120 g / L.
[0040] According to a specific embodiment of the present invention, preferably, the above preparation method specifically comprises the following steps:
[0041] (1) placing a cordierite honeycomb ceramic substrate in pure water, cleaning it with ultrasound, and then drying it; placing the dried cordierite in an alkaline solution, etching the honeycomb cordierite, and then cleaning it with pure water and drying it for later use, thereby obtaining a pretreated honeycomb frame carrier;
[0042] (2) mixing a titanium source precursor, a silicon source precursor and an organic alcohol to obtain a mixed solution, performing a hydrothermal reaction, taking out the material, washing it, filtering it, and performing a first drying and a first calcination to obtain Ti-Si modified TiO2 hollow microspheres;
[0043] (3) adding water to Ti-Si modified TiO2 hollow microspheres, vanadium source precursor, tungsten source precursor, binder, dispersant, pore-forming agent, and buffer and then ball milling to obtain a coated catalyst slurry;
[0044] (4) The coated catalyst slurry is coated on the pretreated honeycomb frame carrier, and the internal channel of the carrier is purged with compressed air. The carrier is then aged, and after a second drying and a second calcination, a honeycomb ceramic supported denitrification catalyst is obtained.
[0045] The present invention also provides a honeycomb ceramic supported denitration catalyst, which is obtained by the above preparation method.
[0046] According to a specific embodiment of the present invention, preferably, the specific surface area of the denitration catalyst is 65.2-68.1m 2 / g.
[0047] According to a specific embodiment of the present invention, preferably, the strength of the denitration catalyst is 20.3-22.6 MPa.
[0048] The present invention also provides a flue gas denitration method, which utilizes the honeycomb ceramic supported denitration catalyst to perform denitration treatment on the flue gas, wherein the flue gas contains nitrogen oxides.
[0049] According to a specific embodiment of the present invention, preferably, the reaction temperature of the denitration treatment is 300-500°C, more preferably 420-500°C, and further preferably 460-500°C.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] (1) The present invention provides Ti-Si modified TiO2 hollow microspheres. In the process of doping SiO2 into TiO2, the Ti in the TiO2 lattice 4+ Easily affected by Si with a smaller radius 4+ The TiO2 is replaced by the SiO2 to form a new Ti-Si solid solution structure, which can bring the following advantages: on the one hand, it is precisely because of the formation of the new Ti-Si crystal phase that the high-temperature thermal stability of the TiO2 carrier is significantly improved, so that the prepared denitrification catalyst can maintain high activity in an environment of 300-500°C; on the other hand, due to the different atomic radii of the two elements, lattice defects are caused after the replacement, which is conducive to the generation of oxygen vacancies.
[0052] (2) The present invention utilizes Ti-Si modified TiO2 hollow microspheres prepared by a hydrothermal method to encapsulate organic alcohol in titanium dioxide, and forms more reaction microspaces and a larger specific surface area through the first calcination, thereby improving the distribution of active ingredients on the surface.
[0053] (3) The denitration catalyst preparation method provided by the present invention supplements vanadium and tungsten elements after the first calcination treatment. Because Ti-Si modified TiO2 hollow microspheres contain numerous lattice defects, supplementing them with vanadium and tungsten elements before the second calcination can stabilize the bond between vanadium and tungsten and the substrate. This also makes the active ingredients within the microspheres more evenly distributed, helping the catalyst maintain high denitration activity and efficiency over a long period of time.
[0054] (4) The preparation process of the honeycomb ceramic-supported denitration catalyst provided by the present invention is simple and highly operable. Alkali etching of the cordierite increases not only its external specific surface area but also its surface roughness, facilitating subsequent coating. The present invention directly coats the catalyst layer on the honeycomb channel surface, drying, and calcining it to obtain the denitration catalyst. This eliminates the need to first coat the honeycomb surface to form a coating layer and then impregnate the active ingredient.
[0055] (5) The cordierite honeycomb ceramic-supported denitrification catalyst provided by the present invention has high strength, increased geometric specific surface area, high molding rate, low production cost, low transportation damage rate, and reduced catalyst loading space. DETAILED DESCRIPTION
[0056] In order to have a clearer understanding of the technical features, objectives and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be understood as limiting the scope of implementation of the present invention.
[0057] In each example and comparative example, all other chemicals used were commercially available chemically pure reagents. The catalysts prepared in the examples and comparative examples were evaluated using the following assay methods:
[0058] (1) Specific surface area
[0059] The specific surface area of the samples was determined by the BET adsorption method.
[0060] (2) Denitrification efficiency
[0061] The catalysts prepared in the examples and comparative examples were used as denitration catalysts, and the flue gas was denitrated according to the following flue gas denitration method:
[0062] The catalyst was cut into a column of φ30×150mm and placed in a fixed bed reactor. A mixed gas containing oxygen and nitrogen was introduced and heated. At the same time, flue gas was introduced to allow the flue gas to fully contact the catalyst for denitrification. The concentration of each component in the flue gas and exhaust gas was measured by a flue gas analyzer, and the NO x Conversion rate = (NO in flue gas x Concentration-NO in exhaust gas x concentration) / NO in flue gas x Concentration, calculated NO x conversion rate.
[0063] Among them, the flue gas analyzer is a continuous online flue gas analyzer, model is Siemens ULTRAMAT23; the content of each component in the flue gas is: ammonia is 350mg / Nm 3 , nitric oxide is 350mg / Nm 3 ; Using a standard gas meter, the O2 content in the reactor is 3% (V), the NH3 and NO contents are both 5% (V), and nitrogen is the balance gas; the manufacturers of NO and NH3 are both Dalian Date Gas Co., Ltd.; the pressure of O2 is 0.4-0.6MPa; the purity of N2 is 99.0% (V), and the pressure is 0.4-0.6MPa.
[0064] Example 1
[0065] This embodiment provides a method for preparing a honeycomb ceramic supported denitration catalyst, which specifically includes the following steps:
[0066] (1) Pretreatment of cordierite honeycomb ceramic matrix
[0067] A 100-mesh cordierite honeycomb ceramic substrate was placed in pure water and ultrasonically cleaned for 30 minutes. It was then placed in a drying oven at 90°C and dried for 2.5 hours. After natural cooling, it was placed in a 2.0 mol / L sodium hydroxide solution at 80°C. After etching for 4 hours, it was taken out, washed with pure water, and dried for later use.
[0068] (2) Preparation of coating slurry
[0069] 100 g of tetrabutyl titanate (calculated as TiO2), 4 g of sodium metasilicate (calculated as SiO2), and 400 ml of ethylene glycol were mixed and stirred, then placed in a reactor. After hydrothermal reaction at a reaction temperature of 150°C for 24 hours, the material was taken out for washing and filtering, then placed at 110°C and dried for 3 hours. After taking out the sample, it was placed in a 420°C environment for roasting for 10 hours to obtain Ti-Si modified TiO2 hollow microspheres; the Ti-Si modified TiO2 hollow microspheres were mixed with 2.0 g of ammonium tungstate (calculated as WO3), 4.0 g of ammonium metavanadate (calculated as V2O5), 1.0 g of polyoxyethylene, 3.0 g of hydroxypropyl cellulose, and 1.5 g of polyethylene glycol, added with deionized water and mechanically stirred, and the pH value of the material was adjusted to 9.0 with ammonia water to make a mud material with a solid content of 40%. The mud material was ball-milled for 1.5 hours to obtain a coated catalyst slurry.
[0070] (3) Loading of coating liquid
[0071] The coated catalyst slurry prepared in step (2) is coated on the honeycomb frame carrier, and the coating amount of the slurry is 60 g / L. The internal channel of the carrier is purged with compressed air. The carrier is placed in an environment of 20°C for aging for 24 hours, dried at 60°C for 50 hours, and calcined at 520°C for 4 hours to obtain a honeycomb ceramic supported denitrification catalyst.
[0072] The specific surface area of the catalyst obtained above is 66.5m 2 / g, strength is 21.8MPa. Reaction conditions: The volume space velocity of the mixed gas containing oxygen and nitrogen is 12000h -1 , temperature 350℃, NO x Conversion rate 99.5%.
[0073] Example 2
[0074] This embodiment provides a method for preparing a honeycomb ceramic supported denitration catalyst, which specifically includes the following steps:
[0075] (1) Pretreatment of cordierite honeycomb ceramic matrix
[0076] A 40-mesh cordierite honeycomb ceramic substrate was placed in pure water and ultrasonically cleaned for 20 minutes. It was then placed in a drying oven at 90°C and dried for 3 hours. After natural cooling, it was placed in a 4.0 mol / L potassium hydroxide solution at 150°C. After etching for 4 hours, it was taken out, washed with pure water, and dried for later use.
[0077] (2) Preparation of coating slurry
[0078] 100 g of tetrabutyl titanate (calculated as TiO2), 3 g of sodium silicate (calculated as SiO2) and 800 ml of ethylene glycol were mixed and stirred, then placed in a reactor. After hydrothermal reaction at a reaction temperature of 150°C for 24 hours, the material was taken out for washing and filtering, then placed at 110°C and dried for 3 hours. After taking out the sample, it was placed in a 600°C environment for roasting for 3 hours to obtain Ti-Si modified TiO2 hollow microspheres; the Ti-Si modified TiO2 hollow microspheres were mixed with 6.0 g of ammonium tungstate (calculated as WO3), 2.0 g of ammonium vanadate (calculated as V2O5), 1.0 g of polyoxyethylene, 1.5 g of hydroxypropyl cellulose and 0.8 g of polyethylene glycol, added with deionized water and mechanically stirred, and the pH value of the material was adjusted to 9.0 with ammonia water to make a mud material with a solid content of 40%. The mud material was ball-milled for 1 hour to obtain a coated catalyst slurry.
[0079] (3) Loading of coating liquid
[0080] The coated catalyst slurry prepared in step (2) is coated on the honeycomb frame carrier, and the coating amount of the slurry is 90 g / L. The internal channel of the carrier is purged with compressed air. The carrier is placed in an environment of 30°C for aging for 15 hours, dried at 80°C for 40 hours, and calcined at 650°C for 2 hours to obtain a honeycomb ceramic supported denitrification catalyst.
[0081] The specific surface area of the catalyst obtained above is 68.1m 2 / g, strength is 20.3MPa. Reaction conditions: The volume space velocity of the mixed gas containing oxygen and nitrogen is 12000h -1 , temperature 370℃, NO x Conversion rate 99.8%.
[0082] Example 3
[0083] This embodiment provides a method for preparing a honeycomb ceramic supported denitration catalyst, which specifically includes the following steps:
[0084] (1) Pretreatment of cordierite honeycomb ceramic matrix
[0085] A 150-mesh cordierite honeycomb ceramic substrate was placed in pure water and ultrasonically cleaned for 50 minutes. The substrate was then placed in a drying oven at a controlled temperature of 110°C. After drying for 3 hours, the substrate was taken out and naturally cooled in a 2.0 mol / L sodium hydroxide solution at a controlled temperature of 130°C. The substrate was etched for 2 hours and then taken out and washed with pure water and dried for later use.
[0086] (2) Preparation of coating slurry
[0087] 100 g of tetraisopropyl titanate (calculated as TiO2), 5 g of sodium silicate (calculated as SiO2) and 1000 ml of ethanol were mixed and stirred, then placed in a reactor. After hydrothermal reaction at a reaction temperature of 160°C for 22 hours, the material was taken out for washing and filtering, then placed at 100°C and dried for 4 hours. After taking out the sample, it was placed in a 500°C environment for roasting for 5 hours to obtain Ti-Si modified TiO2 hollow microspheres; the Ti-Si modified TiO2 hollow microspheres were mixed with 5.0 g of ammonium metatungstate (calculated as WO3), 3.0 g of ammonium metavanadate (calculated as V2O5), 1.5 g of polymethyl methacrylate, 2.0 g of carboxymethyl cellulose and 1.0 g of polyacrylamide, deionized water was added and mechanically stirred to mix, and the pH value of the material was adjusted to 10.0 with ammonia water to make a mud with a solid content of 35%. The mud was ball-milled for 2.0 hours to obtain a coated catalyst slurry.
[0088] (3) Loading of coating liquid
[0089] The coated catalyst slurry prepared in step (2) is coated on the honeycomb frame carrier, and the coating amount of the slurry is 30 g / L. The internal channel of the carrier is purged with compressed air. The carrier is placed in an environment of 30°C for aging for 15 hours, dried at 80°C for 40 hours, and calcined at 500°C for 3 hours to obtain a honeycomb ceramic supported denitrification catalyst.
[0090] The specific surface area of the catalyst obtained above is 66.9m 2 / g, strength is 22.6MPa. Reaction conditions: The volume space velocity of the mixed gas containing oxygen and nitrogen is 12000h -1 , temperature 460℃, NO x Conversion rate 98.3%.
[0091] Example 4
[0092] This embodiment provides a method for preparing a honeycomb ceramic supported denitration catalyst, which specifically includes the following steps:
[0093] (1) Pretreatment of cordierite honeycomb ceramic matrix
[0094] An 80-mesh cordierite honeycomb ceramic substrate was placed in pure water and ultrasonically cleaned for 40 minutes. The substrate was then placed in a drying oven at 90°C and dried for 2.5 hours. The substrate was then naturally cooled and placed in a 3.0 mol / L sodium hydroxide solution at 130°C. The substrate was etched for 3 hours and then taken out, washed with pure water, and dried for later use.
[0095] (2) Preparation of coating slurry
[0096] 100 g of tetraisopropyl titanate (calculated as TiO2), 5 g of sodium silicate (calculated as SiO2) and 600 ml of ethanol were mixed and stirred, then placed in a reactor. After hydrothermal reaction at a reaction temperature of 180°C for 15 hours, the material was taken out for washing and filtering, then placed at 100°C and dried for 8 hours. After taking out the sample, it was placed in a 500°C environment for roasting for 6 hours to obtain Ti-Si modified TiO2 hollow microspheres; the Ti-Si modified TiO2 hollow microspheres were mixed with 3.0 g of ammonium metatungstate (calculated as WO3), 0.5 g of ammonium metavanadate (calculated as V2O5), 0.5 g of polyethylene oxide, 1.2 g of hydroxypropyl cellulose and 1.5 g of polyvinyl pyrrolidone, deionized water was added and mechanically stirred, and the pH value of the material was adjusted to 9.0 with ammonia water to make a mud material with a solid content of 30%. The mud material was ball-milled for 1.5 hours to obtain a coated catalyst slurry.
[0097] (3) Loading of coating liquid
[0098] The coated catalyst slurry prepared in step (2) is coated on the honeycomb frame carrier, and the coating amount of the slurry is 120 g / L. The internal channel of the carrier is purged with compressed air. The carrier is placed in an environment of 30°C for aging for 20 hours, dried at 60°C for 50 hours, and calcined at 480°C for 8 hours to obtain a honeycomb ceramic supported denitrification catalyst.
[0099] The specific surface area of the catalyst obtained above is 65.8m 2 / g, strength is 21.2MPa. Reaction conditions: The volume space velocity of the mixed gas containing oxygen and nitrogen is 12000h -1 , temperature 420℃, NO x Conversion rate 99.1%.
[0100] Example 5
[0101] This embodiment provides a method for preparing a honeycomb ceramic supported denitration catalyst, which specifically includes the following steps:
[0102] (1) Pretreatment of cordierite honeycomb ceramic matrix
[0103] A 120-mesh cordierite honeycomb ceramic substrate was placed in pure water and ultrasonically cleaned for 50 minutes. The substrate was then placed in a drying oven at a controlled temperature of 105°C. After drying for 2 hours, the substrate was taken out and naturally cooled in a 1.0 mol / L sodium hydroxide solution at a controlled temperature of 140°C. The substrate was etched for 1.5 hours and then taken out. The substrate was washed with pure water and dried for later use.
[0104] (2) Preparation of coating slurry
[0105] 100 g of tetraisopropyl titanate (calculated as TiO2), 7 g of sodium metasilicate (calculated as SiO2), and 500 ml of ethylene glycol were mixed and stirred, then placed in a reactor. After hydrothermal reaction at a reaction temperature of 170°C for 18 hours, the material was taken out for washing and filtering, then placed at 90°C and dried for 15 hours. After taking out the sample, it was placed in a 460°C environment for roasting for 8 hours to obtain Ti-Si modified TiO2 hollow microspheres; the Ti-Si modified TiO2 hollow microspheres were mixed with 1.0 g of ammonium metatungstate (calculated as WO3), 4.0 g of ammonium metavanadate (calculated as V2O5), 1.5 g of polymethyl methacrylate, 2.0 g of carboxymethyl cellulose, and 1.0 g of polyacrylamide, and mechanically stirred with deionized water. The pH value of the material was adjusted to 10.0 with ammonia water to make a mud material with a solid content of 35%. The mud material was ball-milled for 2.0 hours to obtain a coated catalyst slurry.
[0106] (3) Loading of coating liquid
[0107] The coated catalyst slurry prepared in step (2) is coated on the honeycomb frame carrier, and the coating amount of the slurry is 50 g / L. The internal channel of the carrier is purged with compressed air. The carrier is placed in an environment of 30°C for aging for 15 hours, dried at 80°C for 40 hours, and calcined at 500°C for 3 hours to obtain a honeycomb ceramic supported denitrification catalyst.
[0108] The specific surface area of the catalyst obtained above is 66.2m 2 / g, strength is 22.6MPa. Reaction conditions: The volume space velocity of the mixed gas containing oxygen and nitrogen is 12000h -1 , temperature 360℃, NO x Conversion rate 99.5%.
[0109] Comparative Example 1
[0110] This comparative example provides a method for preparing a denitration catalyst, which differs in that unmodified anatase nano-titanium dioxide is directly used as a raw material, and specifically comprises the following steps:
[0111] (1) Pretreatment of cordierite honeycomb ceramic matrix
[0112] A 100-mesh cordierite honeycomb ceramic substrate was placed in pure water and ultrasonically cleaned for 30 minutes. It was then placed in a drying oven at 90°C and dried for 2.5 hours. After natural cooling, it was placed in a 2.0 mol / L sodium hydroxide solution at 80°C. After etching for 4 hours, it was taken out, washed with pure water, and dried for later use.
[0113] (2) Preparation of coating slurry
[0114] 100 g of TiO2 was mixed with 2.0 g of ammonium tungstate (calculated as WO3), 4.0 g of ammonium metavanadate (calculated as V2O5), 1.0 g of polyoxyethylene, 3.0 g of hydroxypropyl cellulose, 1.5 g of polyethylene glycol, and deionized water under mechanical stirring. The pH value of the material was adjusted to 9.0 with ammonia water to prepare a slurry with a solid content of 40%. The slurry was ball-milled for 1.5 h to obtain a coated catalyst slurry.
[0115] (3) Loading of coating liquid
[0116] The coated catalyst slurry prepared in step (2) is coated on the honeycomb frame carrier, and the coating amount of the slurry is 60 g / L. The internal channel of the carrier is purged with compressed air. The carrier is placed in an environment of 20°C for aging for 24 hours, dried at 60°C for 50 hours, and calcined at 520°C for 4 hours to obtain a denitration catalyst.
[0117] The specific surface area of the obtained catalyst is 52.3 m 2 / g, strength is 21.8MPa. Reaction conditions: The volume space velocity of the mixed gas containing oxygen and nitrogen is 12000h -1 , temperature 350℃, NO x Conversion rate 97.9%.
[0118] Comparative Example 2
[0119] This comparative example provides a preparation method of a denitration catalyst, which differs in that the modified titanium dioxide is not calcined after the hydrothermal reaction, but is directly subjected to ball milling mixing. The method specifically comprises the following steps:
[0120] (1) Pretreatment of cordierite honeycomb ceramic matrix
[0121] A 40-mesh cordierite honeycomb ceramic substrate was placed in pure water and ultrasonically cleaned for 20 minutes. It was then placed in a drying oven at 90°C and dried for 3 hours. After natural cooling, it was placed in a 4.0 mol / L potassium hydroxide solution at 150°C. After etching for 4 hours, it was taken out, washed with pure water, and dried for later use.
[0122] (2) Preparation of coating slurry
[0123] 100 g of tetrabutyl titanate (calculated as TiO2), 3.0 g of sodium silicate (calculated as SiO2) and 800 ml of ethylene glycol were mixed and stirred, then placed in a reactor. After hydrothermal reaction at a reaction temperature of 150°C for 24 hours, the material was taken out for washing and filtration, and then placed at 110°C and dried for 3 hours to obtain oxide microspheres. The oxide microspheres were mixed with 6.0 g of ammonium tungstate (calculated as WO3), 2.0 g of ammonium vanadate (calculated as V2O5), 1.0 g of polyoxyethylene, 1.5 g of hydroxypropyl cellulose and 0.8 g of polyethylene glycol, added with deionized water and mechanically stirred, and the pH value of the material was adjusted to 9.0 with ammonia water to prepare a mud material with a solid content of 40%. The mud material was ball-milled for 1 hour to obtain a coated catalyst slurry.
[0124] (3) Loading of coating liquid
[0125] The coated catalyst slurry prepared in step (2) is coated on the honeycomb frame carrier, and the coating amount of the slurry is 90 g / L. The internal channel of the carrier is purged with compressed air. The carrier is placed in an environment of 30°C for aging for 15 hours, dried at 80°C for 40 hours, and calcined at 650°C for 2 hours to obtain a denitration catalyst.
[0126] The specific surface area of the obtained catalyst is 41.5 m 2 / g, strength is 20.3MPa. Reaction conditions: The volume space velocity of the mixed gas containing oxygen and nitrogen is 12000h -1 , temperature 370℃, NO x Conversion rate 95.6%.
[0127] Comparative Example 3
[0128] This comparative example provides a method for preparing a denitration catalyst, the difference being that the silicon source used in modifying titanium dioxide is replaced with a cerium source, and specifically comprises the following steps:
[0129] (1) Pretreatment of cordierite honeycomb ceramic matrix
[0130] A 150-mesh cordierite honeycomb ceramic substrate was placed in pure water and ultrasonically cleaned for 50 minutes. The substrate was then placed in a drying oven at a controlled temperature of 110°C. After drying for 3 hours, the substrate was taken out and naturally cooled in a 2.0 mol / L sodium hydroxide solution at a controlled temperature of 130°C. The substrate was etched for 2 hours and then taken out and washed with pure water and dried for later use.
[0131] (2) Preparation of coating slurry
[0132] 100 g of tetraisopropyl titanate (calculated as TiO2), 5.0 g of cerium nitrate (calculated as CeO2) and 1000 ml of ethanol were mixed and stirred and placed in a reactor. After hydrothermal reaction at a reaction temperature of 160°C for 22 hours, the material was taken out for washing and filtering, then placed at 100°C and dried for 4 hours. After taking out the sample, it was placed in a 500°C environment for roasting for 5 hours to obtain oxide microspheres; the oxide microspheres were mixed with 5.0 g of ammonium metatungstate (calculated as WO3), 3.0 g of ammonium metavanadate (calculated as V2O5), 1.5 g of polymethyl methacrylate, 2.0 g of carboxymethyl cellulose and 1.0 g of polyacrylamide, deionized water was added and mechanically stirred to mix, the pH value of the material was adjusted to 10.0 with ammonia water to make a mud with a solid content of 35%, and the mud was ball-milled for 2.0 hours to obtain a coated catalyst slurry.
[0133] (3) Loading of coating liquid
[0134] The coated catalyst slurry prepared in step (2) is coated on the honeycomb frame carrier, and the coating amount of the slurry is 30 g / L. The internal channel of the carrier is purged with compressed air. The carrier is placed in an environment of 30°C for aging for 15 hours, dried at 80°C for 40 hours, and calcined at 500°C for 3 hours to obtain a denitration catalyst.
[0135] The specific surface area of the catalyst obtained above is 66.7m 2 / g, strength is 22.6MPa. Reaction conditions: The volume space velocity of the mixed gas containing oxygen and nitrogen is 12000h -1 , temperature 460℃, NO x The conversion rate was 93.6%.
[0136] The catalyst prepared by the preparation method provided by the present invention can maintain a denitration efficiency of more than 98.0% at a reaction temperature of 300-500°C. Among them, at a reaction temperature of 460°C, 98.3% of NO x In addition, the catalyst is particularly suitable for reaction space velocities up to 12000h -1 In the present invention, the inventors believe through research and analysis that: using cordierite honeycomb ceramics as a carrier, there are more gas flow channels per unit cross-section, which can greatly increase the geometric specific surface area of the catalyst and reduce the gas surface velocity; at the same time, the present invention uses a hydrothermal method to synthesize modified TiO2 microspheres, and the Ti-Si modified TiO2 hollow microspheres obtained by further calcination have rich internal micropores, which improves the distribution of catalytically active components, so that the prepared honeycomb ceramic-loaded denitrification catalyst has a larger specific surface area, the applicable catalytic reaction temperature is higher, and the denitrification efficiency is improved.
Claims
1. A method for preparing a honeycomb ceramic supported denitrification catalyst, wherein: The method comprises the following steps: (1) placing a cordierite honeycomb ceramic substrate in an alkaline solution for etching to obtain a pretreated honeycomb frame carrier; (2) mixing a titanium source precursor, a silicon source precursor and an organic alcohol to obtain a mixed solution, performing a hydrothermal reaction, and obtaining Ti-Si modified TiO2 hollow microspheres after a first drying and a first calcination; (3) adding water to Ti-Si modified TiO2 hollow microspheres, vanadium source precursor, tungsten source precursor, binder, dispersant, pore-forming agent, and buffer and then ball milling to obtain a coated catalyst slurry; (4) coating the coated catalyst slurry onto the pretreated honeycomb frame support, and then aging, second drying, and second calcining to obtain a honeycomb ceramic supported denitrification catalyst; Wherein, the mass ratio of the silicon source precursor to the titanium source precursor is (3-7):100; The volume ratio of the organic alcohol to the titanium source precursor is (3-10):1; The mass ratio of the vanadium source precursor to the titanium source precursor is (0.2-6.0):100; The mass ratio of the tungsten source precursor to the titanium source precursor is (0.5-8.0):100; The mass of the titanium source precursor is calculated as TiO2, the mass of the silicon source precursor is calculated as SiO2, the mass of the vanadium source precursor is calculated as V2O5, and the mass of the tungsten source precursor is calculated as WO3.
2. The preparation method according to claim 1, wherein The titanium source precursor includes tetrabutyl titanate and / or tetraisopropyl titanate; The silicon source precursor includes sodium silicate and / or sodium metasilicate.
3. The preparation method according to claim 1, wherein The vanadium source precursor includes ammonium metavanadate and / or ammonium vanadate.
4. The preparation method according to claim 1, wherein The tungsten source precursor includes ammonium paratungstate and / or ammonium metatungstate.
5. The preparation method according to claim 1, wherein The mass ratio of the binder, dispersant, pore-forming agent and titanium source precursor is (0.5-5.0):(0.2-3):(0.2-2):100, wherein the mass of the titanium source precursor is calculated as TiO2.
6. The preparation method according to claim 1, wherein In step (2), the temperature of the hydrothermal reaction is 140-220° C., and the time of the hydrothermal reaction is 6-30 hours; the temperature of the first calcination is 400-680° C., and the time of the first calcination is 2-10 hours; In step (4), the second roasting temperature is 450-650° C., and the second roasting time is 2-8 hours; the aging temperature is 20-40° C., and the aging time is 12-48 hours.
7. A honeycomb ceramic supported denitration catalyst, obtained by the preparation method according to any one of claims 1 to 6.
8. The denitration catalyst according to claim 7, wherein: The specific surface area of the denitration catalyst is 65.2-68.1m 2 / g.
9. A flue gas denitration method, comprising: utilizing the honeycomb ceramic supported denitration catalyst according to claim 7 or 8 to denitrate the flue gas, wherein: The flue gas contains nitrogen oxides.
10. The flue gas denitrification method according to claim 9, wherein: The reaction temperature of the denitration treatment is 300-500°C.
Citation Information
Patent Citations
Low temperature SCR catalyst taking Ce-doped TiO2 as carrier and preparation method thereof
CN101721993B
F-doped SCR catalyst, preparation method and application thereof to catalytic denitration
CN106552652A